GEOTECHNICAL PROPERTIES OF MARL ASSOCIATED WITH EZEAKU FORMATION IN AFIKPO AREA, SOUTHEASTERN NIGERIA, IN RELATION TO AGGREGATE QUALITY ASSESSMENT - ONYEKURU S.O; OWONARO B.J; OKEKE O.C (International Journal of Advanced Academic Research, 2019)
The use of marl deposit as construction material has recently attracted some attention to both government and construction companies, hence the evaluation of the geotechnical properties and aggregate quality assessment of the deposit in the Afikpo area was conducted to determine its suitability as aggregate for concrete and highway pavement. The Marl deposit belong to the Ezeaku Formation, this was confirmed from the field observations and description which shows that they are of dark grey to black shale, sandstone, subordinate limestone and siltstone deposited by shallow marine environment. Physico-mechanical properties of the rock shows that the specific gravity of the marl sample is 2.58 %, the water absorption is 1.90 %, the Aggregate Crushing Value (ACV) of the marl sample is 23.50%, the Los Angeles Abrasion Value (LAAV) is 42.70 % and Aggregate Impact Value (AIV) is 29.40 % while the Atterberg Limit Test are Liquid Limit 29.50 %, Plasticity Index 4.60% with Free Swell 10% and Linear Shrinkage 0.30 %. On these bases of low Atterberg Limit values and favourable physico-mechanical properties, the marl in Afikpo area is a good aggregate material for highway pavements and concrete
Keywords: Marl deposit; Properties; Aggregate; Physico-mechanical; Atterberg limit; Highway pavement; Concrete